The Relevance of Modern Islamic Boarding Schools with Ulama Cadre According to Imam Zarkasyi (1910-1985) - Yusutria, Yusutria; Kistoro, Hanif Cahyo Adi; Azwar, Azwar (Universitas Islam Negeri Raden Intan Lampung, 2021)
Imam Zarkasyi was a figure who gave birth to the modern pesantren and ulama cadre in Indonesia. This review is based on literature research with a historical approach. The sources of information depart from the biography and the concept of thought, the methods and information instrumentation from books, papers, posts, magazines, websites, and other types of documentation. The information was analyzed using management systems that can draw information from documentation. Relevant data sourced from works on the topic were analyzed descriptively. The research results are 1) based on